(untitled) (Portuguese Journal of Family Medicine and General Practice, 2014)
TRIMETHYLAMINURIA OR FISH MALODOR SYNDROME – CASE REPORT AND RELEVANCE TO PRACTICE “Fish malodour syndrome” or trimethylaminuria is an infrequent and probably under-diagnosed metabolic disorder characterized by a decaying fish odour in body secretions with potentially severe psychosocial complications. This article presents a patient with trimethylaminuria, with the typical body odour, selective anosmia, and seafood allergy. Her parents intuitively applied adequate treatment that probably prevented adverse consequences. The diagnosis is based on clinical symptoms and is confirmed either by genetic testing or urinary levels of trimethylamine oxide and trimethylamine. Treatment aims to reduce body odour and prevent complications, which determine prognosis. This article aims to increase awareness of the condition and present information relevant to the family physician.